The War of My Generation : Youth Culture and the War on Terror - Kieran, David, 1978- (Book collections on Project MUSE., 2015)
In the years since the 9/11 attacks, members of the millennial and post-millennial generation have come of age in a moment marked by increased anxiety about terrorism, two protracted wars, and policies that have raised quesions about the strategies of the United States abroad and at home. Drawing from a variety of disciplines, The War of My Generation is the first essay collection to focus specifically on how the terrorist attacks and their aftermath have shaped this new generation of Americans. -- Provided by publisher.